Epigenetic dysregulation in pancreatic cancer: emerging biomarkers and clinical applications - Sultana, Hina; Solomon, Abhishikt David; Wani, Atif Khurshid; Shukla, Surendra K. (Frontiers in Epigenetics and Epigenomics, 2025)
Pancreatic cancer, in particular pancreatic ductal adenocarcinoma (PDAC), is one of the most lethal malignancies with delayed diagnosis, aggressive nature, and profound therapeutic resistance. Recent research has emphasized epigenetic dysregulation not as a bystander but as a driving force in pancreatic tumorigenesis, progression, metastasis, and immune evasion. This review presents a detailed analysis of the multifaceted functions of epigenetic mechanisms like DNA methylation, histone modifications, and non-coding RNAs in shaping the pancreatic cancer epigenome. We discuss how these alterations fuel tumor heterogeneity, modulate the tumor microenvironment, and interact with key oncogenic mutations like KRAS and TP53. Further, we discuss the potential of epigenetic alterations as diagnostic, prognostic, and predictive biomarkers with an emphasis on their application in liquid biopsies. Finally, we evaluate current and prospective epigenetic therapies, their cooperation with chemotherapy and immunotherapy, and the prospects of new approaches such as CRISPR-based epigenome editing and personalized epigenetic profiling. Together, these findings point to the epigenome as a powerful window of opportunity for understanding, diagnosing, and eventually targeting pancreatic cancer.